Comparison of Farmers’ Term of Trades in the Animal Husbandry and Fishery Subsectors in South Sulawesi - Aditya Adlu Rahman; Sri Mardiyati; Nurdin, Nurdin; Nadir, Nadir (Cita konsultindo, 2025)
This study aims to analyze the trend of Farmers’ Term of Trades in the animal husbandry and fisheries sub-sectors, and to analyze the comparison of Farmers’ Term of Trades in the animal husbandry and fisheries sub-sectors in South Sulawesi Province. This study is a type of quantitative research. The type of data is secondary data (monthly time series), obtained from the Central Statistics Agency of Indonesia, from January 2020 to November 2024. Data analysis uses trend analysis and real difference tests (t-tests). The results of this study indicate that the Farmers’ Term of Trade (FTT) of the animal husbandry sub-sector in South Sulawesi Province during the period 2020-2024 experienced an increasing trend of 0.2109 per month, so that the level of farmer welfare tended to increase during that period. The Farmers’ Term of Trade in the fisheries sub-sector (capture fisheries and aquaculture) also experienced an increasing trend of 0.2556 per month, so that the level of fishermen's welfare also tended to increase during that period. Based on the results of the statistical test (t-test), the comparison of the Farmers’ Term of Trade in the animal husbandry and fisheries sub-sectors did not show a significant difference. The FTT of capture fishermen increased by 0.2423 while the FTT of aquaculture fishermen increased by 0.2641. The FTT of capture fishermen is proven to be significantly higher than the FTT of aquaculture fishermen, so that capture fishermen tend to be more prosperous.